LITERATURE REVIEW: TEKNOLOGI EDIBLE COATING DALAM MEMPERPANJANG UMUR SIMPAN PANGAN: Literature Review: Technology of Edible Coating for Extending Food Shelf Life - KIKI NATASIA; Khairunnisa Nadya Risti; Dinar Putri Rahmawati (Poltekkes Kemenkes Yogyakarta, 2026)
Background: Quality degradation of fresh and processed foods remains a major issue in Indonesia due to its tropical climate that accelerates spoilage. Edible coatings and nano-/micro-encapsulation are innovative, natural-based preservation technologies designed to extend shelf life without synthetic preservatives. This study aims to review their effectiveness and potential application for local food products in small and medium-scale industries. Methods: This descriptive literature review analyzed 5 scientific articles published between 2020 and 2025, retrieved from SINTA, Google Scholar, Scopus, and ScienceDirect databases. The review examined the types of biopolymer materials used, effectiveness in reducing microbial growth and oxidation, and challenges in industrial implementation. Data were analyzed narratively and grouped by key themes for synthesis. Results: Findings show that combining biopolymer-based edible coatings (chitosan, alginate, pectin) with nano-/micro-encapsulation systems can extend product shelf life by 7–10 days and reduce microbial counts by 2–3 log CFU/g. Incorporating tropical essential oils such as lemongrass and clove enhances antimicrobial and antioxidant performance. However, production cost, technological limitations, and nano-material regulations remain obstacles for large-scale adoption. Conclusion: Edible coatings and nano-/micro-encapsulation present promising, eco-friendly alternatives for natural food preservation in tropical regions. Further research on local material optimization, economic feasibility, and consumer acceptance is required before industrial-scale implementation in Indonesia. ABSTRAK Penurunan mutu produk pangan segar dan olahan masih menjadi tantangan utama di Indonesia, terutama karena iklim tropis yang mempercepat proses pembusukan. Penggunaan edible coatings dan nano-/micro-encapsulation merupakan pendekatan inovatif berbasis bahan alami untuk memperpanjang umur simpan tanpa pengawet sintetis. Penelitian ini bertujuan untuk meninjau efektivitas dan potensi penerapan kedua teknologi tersebut pada produk pangan lokal dalam konteks industri kecil dan menengah. Penelitian ini merupakan literature review deskriptif dengan menganalisis 15 artikel ilmiah yang diterbitkan antara tahun 2016–2025, diperoleh melalui database SINTA, Google Scholar, Scopus, dan ScienceDirect. Analisis dilakukan terhadap jenis bahan biopolimer, efektivitas terhadap penurunan mikroba dan oksidasi, serta tantangan penerapan di industri pangan. Data dianalisis secara naratif dan dikategorikan berdasarkan topik utama. Hasil kajian menunjukkan bahwa kombinasi edible coatings berbasis kitosan, alginat, atau pektin dengan sistem nano-/micro-encapsulation mampu memperpanjang umur simpan produk pangan hingga 7–10 hari dan menurunkan pertumbuhan mikroba sebesar 2–3 log CFU/g. Formulasi dengan minyak atsiri tropis seperti serai dan cengkeh meningkatkan aktivitas antimikroba dan antioksidan. Namun, keterbatasan biaya, teknologi, serta regulasi penggunaan bahan nano menjadi kendala utama untuk skala industri. Teknologi edible coatings dan nano-/micro-encapsulation berpotensi tinggi sebagai pengawet alami yang ramah lingkungan dan sesuai untuk produk pangan tropis. Diperlukan penelitian lanjutan untuk menguji bahan lokal, kelayakan ekonomi, dan penerimaan konsumen sebelum diterapkan secara luas di industri pangan Indonesia.